2010
DOI: 10.1111/j.1464-5491.2009.02920.x
|View full text |Cite|
|
Sign up to set email alerts
|

Incorrect and incomplete coding and classification of diabetes: a systematic review

Abstract: This review draws attention to the occurrence and implications of incorrect or incomplete coding or classification of diabetes, particularly in young people. A pragmatic and clinically relevant approach to classification is needed to assist those involved in making decisions about types of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 22 publications
0
52
0
1
Order By: Relevance
“…13,14 Coding may be performed by trained, nonmedical coders using discharge summaries and clinical records, which are often incomplete or poorly reflect all of a patient's relevant diagnoses. In this study, these problems were avoided by allocating AR-DRG codes for each admission only after manually crossreferencing all of the data from the AVU database against the relevant paper and electronic medical records.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Coding may be performed by trained, nonmedical coders using discharge summaries and clinical records, which are often incomplete or poorly reflect all of a patient's relevant diagnoses. In this study, these problems were avoided by allocating AR-DRG codes for each admission only after manually crossreferencing all of the data from the AVU database against the relevant paper and electronic medical records.…”
Section: Discussionmentioning
confidence: 99%
“…T2DM is a complex metabolic disorder developing from insulin resistance later in life, characterized by combination of defects in insulin secretion and action (Shaw et al, 2000). However, there are forms of diabetes that can be less clearly characterized into either type, such as latent autoimmune diabetes in adults Stone et al, 2010). Approximately 10% of phenotypic type 2 diabetic patients are positive for at least one of the islet autoantibodies, and this group is often referred to as latent autoimmune diabetes in adults (Naik et al, 2009).…”
Section: Autoimmune Mechanisms In T2dmmentioning
confidence: 99%
“…We found that 13% of individuals who had been diagnosed with diabetes in young adult life had an aetiology for diabetes other than classical type 1 or type 2 diabetes. Apart from accuracy of diagnostic coding [8], this will affect their management and, for those with genetic forms of diabetes, has implications for the screening of relatives. Our study suggests there are at least 5,000 cases of HNF1A-MODY in the UK of whom nearly 90% remain unidentified [1].…”
mentioning
confidence: 99%